Shaikh daud of Sunur: Conflict between Reformists and the Shaá¹á¹ÄrÄ«yah Sufi Order in Rantau Pariaman in the First Half of the Nineteenth Century - Suryadi, Suryadi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2001)
In the first half of the 19th Century, there once lived an ulama (religious leader) on the west coast of Minangkabau (modern day West Sumatra), named Shaikh Daud (not to be confused with Shaikh Daud Al-Fattani from Pattani, southern Thailand). But many people do not yet know about this man. With the axpectation of Hamka (1967:34), researchers who have studied Islam in West Sumatra have almost never mentioned his name. Hamka only mentions him briefly, saying that Shaikh Daud is one of the ulama from the west coast of Minangkabau who left his birthplace rather than stay to watch the increasing power of the Dutch in his native land.DOI:Â 10.15408/sdi.v8i3.681